ANALISIS YURIDIS PEMBERHENTIAN KEPALA DESA YANG MENJADI TERPIDANA KASUS KORUPSI DI KABUPATEN CILACAP - Persada, Galang Bakti; Samhudi, Gamalel Rifqi (LPPM STIH Awang Long, 2025)
The dismissal of the village head is an important aspect in the running of the village government. Village heads are dismissed for violating the provisions stipulated in the law, one of which is corruption. The dismissal mechanism is often not aligned between the rules and practices in the field. Therefore, this study discusses the mechanism for dismissing village heads who are caught in corruption cases. This study aims to analyze the suitability of the mechanism for dismissing village heads with applicable legal provisions and evaluate its application in practice. The method used is an empirical juridical approach, which examines relevant laws and regulations and combines them with the results of field observations and interviews. The object of this research is the process of dismissal of the Panisihan Village Head, who was permanently dismissed in 2021 before a court decision with permanent legal force in 2023. The results show that administratively, the dismissal process has followed formal procedures through the authorized institution. However, juridically, the permanent dismissal raises issues in the application of the principle of legal certainty because there was no legal basis in the form of a court decision when the dismissal was made. This study concludes that although the government's steps are considered quick in maintaining the stability of the village government, they have not fully fulfilled the requirements of the legal certainty principle.